1998
DOI: 10.1210/endo.139.6.6027
|View full text |Cite
|
Sign up to set email alerts
|

The Xenoestrogen Bisphenol A Induces Growth, Differentiation, and c-fos Gene Expression in the Female Reproductive Tract*

Abstract: The xenoestrogen bisphenol A (BPA) has been shown to mimic estrogen both in vivo and in vitro. BPA stimulates PRL secretion and the expression of a PRL regulating factor from the posterior pituitary in the estrogen-sensitive Fischer 344 rat (F344), but not in Sprague-Dawley (SD) rats. The goal of the present studies was to examine the in vivo actions of BPA on the reproductive tract. The specific objectives were 1) to characterize the short term effects of BPA on cell proliferation and c-fos expression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(75 citation statements)
references
References 32 publications
2
73
0
Order By: Relevance
“…BADGE is also present in sealants used in dentistry (14). Because bisphenol A is a known xenoestrogen (15) and endocrine disrupter, it will therefore be important to monitor the possible environmental implications (16) of BADGE exposure in light of its new function as a PPAR␥ antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…BADGE is also present in sealants used in dentistry (14). Because bisphenol A is a known xenoestrogen (15) and endocrine disrupter, it will therefore be important to monitor the possible environmental implications (16) of BADGE exposure in light of its new function as a PPAR␥ antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies suggest that BBP and BPA exposure during differentiating and developmental stages exert irreversible effects on the reproductive organs as well as on the hypothalamic structures controlling reproductive functions. Very few data, however, are available as to their possible action on the hypothalamo-pituitary-gonadal axis in adults, except one report claiming that injection of BPA induced c-fos expression in the uterus and the vagina of adult ovariectomized (OVX) Fisher 344 rats [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Yet, a direct link between an estrogen membrane binding site (9) and xenoestrogen actions is still a matter of debate. Moreover, despite the great number of studies about nongenomic actions of estrogens, a clear outline of the membrane receptor involved is still elusive.We have chosen three widely used xenoestrogens for our study: bisphenol-A (BPA), which is found in the content of canned food, dental sealants, and composites; diethylstilbestrol (DES), a synthetic estrogen used between the 1940s and the 1970s to prevent miscarriages; and the well-known pesticide (3,(10)(11)(12). We have focused our research on the effect of these agents on the signaling system of pancreatic ␤ cells, which are fundamental for the endocrine pancreas function.…”
mentioning
confidence: 99%